High Incidence of syphilis seroconversion among people living with HIV in Hainan, south China - Kaokao Zhu; Chunyun Lu; Huili Yan; Yuan Qiu; Feng Qiao; Wenting Zhang; Dee Yu (Scientific Reports)
Abstract Globally, people living with HIV (PLHIV) are at a high risk of syphilis transmission, and Hainan Province has one of the highest syphilis rates in China. However, there is no targeted syphilis screening for HIV patients in Hainan, highlighting the need for data to guide public health interventions. This study aims to assess the incidence of seropositive syphilis and its associated factors among PLHIV. A retrospective cohort study was conducted at HIV care facilities in Haikou, China, recruiting adults living with HIV. The diagnosis of syphilis was confirmed through the TRUST and TPPA tests. Univariate logistic regression was employed to compare syphilis rates across groups, while multivariate logistic regression analysis was conducted to identify factors associated with syphilis infection. Of the 650 participants, 461 (70.9%) were men who have sex with men (MSM). The median age at HIV diagnosis was 28 years, with 154 (23.7%) testing positive for syphilis. The incidence of syphilis was the highest in individuals with prior STDs before HIV (43.1%), followed by those with suboptimal HIV antiretroviral therapy (ART) adherence (38.7%) and MSM (29.5%). The study identified that PLHIV who were diagnosed with HIV through voluntary testing (aOR:1.918, 95%CI:1.113–3.306), were MSM (aOR:2.648, 95%CI:1.269–5.524), had suboptimal HIV ART adherence (aOR:2.002, 95%CI:1.060–3.780), had a history of STDs before HIV (aOR:3.025, 95%CI:1.563–5.857), and had a longer duration of HIV ART (aOR:1.431, 95%CI:1.184–1.730) were at a higher risk of syphilis. The incidence of syphilis is high among PLHIV, especially in MSM and individuals with a history of STDs prior to their HIV diagnosis and suboptimal ART adherence, highlighting the need for targeted interventions and regular screening.